The Relationship between Work Motivation and the Performance of Hospital Administration Officers in the Covid-19 Pandemic Era - Devi Pramita Sari; Yeni Tri Utami; Ananda Nur Khasyanah (Proceeding of International Conference on Science, Health, And Technology, 2021)
Hospital Administration Officers have the task of serving patient registration and administrative needs before getting treatment. Covid-19 is a disease whose transmission is very fast due to the corona virus which has caused a pandemic in all countries, especially Indonesia. The Covid-19 Pandemic era is unsettling and raises concerns, especially for hospital administrative officers because they are officers who are at the forefront of their duties at the hospital. Preliminary preliminary surveys show that there are officers who lack motivation in the Covid-19 Pandemic Era. The purpose of this study was to determine the relationship between work motivation and the performance of Hospital Administration Officers in the Pandemic Era. This research was conducted using a quantitative descriptive survey method with a cross sectional study approach. The population and research sample were taken by total sampling, namely all Hospital Administration Officers as many as 8 respondents. The research instrument used a questionnaire and observation guidelines. Quantitative data analysis used the chi-square relationship test. The results of this study from 8 respondents based on the results of the Chi-Square test, the significance of the independent variables, namely work motivation with the dependent variable of the performance of the officers, was 0.003 (p <0.05), so Ho was rejected and it was stated that there was a relationship. The conclusion is that there is a relationship between work motivation and the performance of Hospital Administration Officers in the Pandemic Era. Suggestions should be necessary to maintain hospital policies related to job security guarantees and good working conditions in the era of the Covid-19 pandemic to motivate hospital administration officers to carry out their work.